2021
DOI: 10.1186/s13104-021-05554-3
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility and genetic relatedness of Shigella species isolated from food and human stool samples in Qazvin, Iran

Abstract: Objective The aim of this study was to investigate the genetic relatedness and antimicrobial resistance among Shigella species isolated from food and stool samples. Using cross sectional study method, Shigella spp. were isolated from food and clinical samples using culture-based, biochemical and serological methods. Antimicrobial susceptibility and genetic relatedness among the isolates were evaluated using disk diffusion and RAPD-PCR methods respectively. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…This study found that resistance against trimethoprim-sulfamethoxazole, tetracycline, lineage III strains due to the acquisition of point mutations within the gyrA and parC genes (Hawkey, et al 2021, Phiri, et al 2021, Shad and Shad 2021. It is extremely important to monitor different S. sonnei lineages/sublineages and the antibiotic resistance profile of these strains as the new emerging threat to public health and global concern of food safety (Hawkey, et al 2021, Pakbin, et al 2021a, Pakbin, et al 2021c.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This study found that resistance against trimethoprim-sulfamethoxazole, tetracycline, lineage III strains due to the acquisition of point mutations within the gyrA and parC genes (Hawkey, et al 2021, Phiri, et al 2021, Shad and Shad 2021. It is extremely important to monitor different S. sonnei lineages/sublineages and the antibiotic resistance profile of these strains as the new emerging threat to public health and global concern of food safety (Hawkey, et al 2021, Pakbin, et al 2021a, Pakbin, et al 2021c.…”
Section: Discussionmentioning
confidence: 94%
“…to Shigella and Enterobacteriaceae family (Pakbin, et al 2021c, Torraca, et al 2020. S. sonnei has been regarded as the main cause of shigellosis in developed countries in North America and Europe.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they may be categorized in a single pathovar. However, a considerable distinction is still maintained regarding the clinical significance of Shigella species [1,73]. EIEC and Shigella are unable to ferment lactose, are non-motile, and lysine decarboxylase negative.…”
Section: Enteroinvasive Escherichia Coli (Eiec)mentioning
confidence: 99%
“…EIEC differs from other pathovars of E. coli because it is an obligate intracellular pathogen with neither adherence nor flagella factors [71]. Shigella comprise four species, including S. sonnei, S. flexneri, S. boydii and S. dysenteriae, which are responsible for varying degrees of diarrhea and acute intestinal and extra-intestinal diseases in humans [73,75,76]. EIEC strains primarily elicit watery diarrhea and cause invasive inflammatory colitis [77].…”
Section: Enteroinvasive Escherichia Coli (Eiec)mentioning
confidence: 99%